Mastering VMware Horizon 7 : learn advanced virtualization techniques and strategies and dive deeper into VMware Horizon 7, take responsibility for optimizing your organizations resources! - Oven, Peter von; Coombs, Barry (Packt Publishing, 2016)
Learn advanced desktop virtualization techniques and strategies and dive deeper into VMware Horizon 7, take responsibility for optimizing your end user experience About This Book Build better virtualized services for your users with VMware Horizon 7 Take full advantage of Horizon's range of features for confidence and control in your virtualized solutions Take responsibility for transforming your organization ? this guide will get you started! Who This Book Is For Admins, architects? whatever your role, if you find virtualization a bit of a headache this book is for you. You'll go deep into VMware Horizon and see just what its capable of. It will take you to an advanced level, but at a pace that ensures you're always solving real-world problems. You'll need some experience in desktop management using Windows and Microsoft Office, and familiarity with Active Directory, SQL, Windows Remote Desktop Session Hosting, and VMware vSphere technology. What You Will Learn Successfully configure Horizon 7 for the needs of your users Find out how VMware is perfect for end-user computing delivering virtual desktops, session-based desktops, and hosted applications all from the same platform Learn how to develop, and deploy a complete end-to-end solution Discover how to optimize desktop OS images for virtual desktops Build, optimize, and tune desktop operating systems to deliver a superior end-user experience Explore the Horizon 7 infrastructure, so you can take full advantage of it! In Detail Desktop virtualization can be a bit of a headache. But VMware Horizon 7 changes all that. With a rich and adaptive UX, improved security and a range of useful features for storage and networking optimization, there's plenty to love. But to properly fall in love with it, you need to know how to use it. And that means venturing deeper into the software, taking advantage of its extensive range of features, many of which are underused and underpromoted. This guide will take you through everything you need to know to not only successfully virtualize your desktop infrastructure but also to maintain and optimize the infrastructure to keep all your users happy. We'll show you how to assess and analyze your infrastructure, and how to use that analysis to design a solution that meets your organizational and user needs. Once you've done that, you'll find out how to build your virtualized environment, before deploying your virtualized solution. But more than that, we'll also make ...